Răspuns:
Explicație pas cu pas:
b) 2(x+8) = 5x +1;
2x + 16 = 5x + 1
5x - 2x = 16 - 1
3x = 15
x = 5
__________
c) 3x – 5x =1;
-2x = 1
x = -1/2
__________
d) 2(x - 1) = 3x +3;
2x - 2 = 3x + 3
3x - 2x = -2 - 3
x = -5
_____________
e) -2(5 – 2x) = x;
-10 + 4x = x
4x - x = 10
3x = 10
x = 10/3
______________
f nu este clar
_____________
g) 6-4(x + 3) = 8;
6 - 4x - 12 = 8
6 - 12 - 8 = 4x
4x = -14
x = -14/4 = -7/2
_____________
h) x+1= 3x - 7;
3x - x = 7 + 1
2x = 8
x = 8/2 = 4
____________
i) -2- x = 3 - (2-x);
-2 - x = 3 - 2 + x
x + x = -2 - 3 + 2
2x = -3
x = -3/2
__________
j) 4 = 5x + 2(3 – x)
4 = 5x + 6 - 2x
3x = 4 - 6 = -2
x = -2/3